KEEFEKTIFAN MODEL PROJECT BASED LEARNING TERHADAP HASIL BELAJAR IPAS SISWA PADA MATERI RANTAI MAKANAN KELAS V DI SDN SINDANG 01 KAB TEGAL: Penelitian Kuantitatif - Zyan Fadlika Maula Kusuma Fadlika; Arfilia Wijayanti; Bagus Ardi Saputro (STKIP Subang, 2024)
The implementation of learning in the classroom by the teacher greatly influences the active learning process and the achievement of student learning outcomes. At the time of the initial interview, there were still 55% of students whose learning outcomes had not yet been completed. The problem of this research is